Attention Deficit Hyperactivity Disorder: A Neglected Issue in the Developing World - Chinawa, J. M. (Hindawi Publishing Corporation, 2014)
Background. Attention deficit hyperactivity disorder (ADHD) is a neglected illness in a developing country. Objectives. The objectives of this study are to investigate the prevalence and pattern of ADHD among children in a Nigeria. Methods. A structured self-administered questionnaire was used to collect information from the parents of children (and older children) who attended children outpatients' clinic during the study period. The DSM-IV-TR diagnostic criteria for attention deficit hyperactivity disorder were used. Results. Two hundred and seventy-three (273) out of 282 questionnaires were filled completely, giving a response rate of 96.8%. Nine (9) children fulfilled the stated criteria for ADHD giving a prevalence rate of 3.2%. There is no association between gender and ADHD (P = 0.784). Conclusions. The prevalence of ADHD in our setting is 3.2%, which is similar to that obtained elsewhere in the world.